Tensile and Flexural Behavior of Ultra-High Performance Concrete (UHPC) under Impact Loading. (July 2021) - Yao, Yiming; Silva, Flavio A; Butler, Marko; Mechtcherine, Viktor; Mobasher, Barzin
Highlights: Flexural impact and high-speed tension tests of UHPC specimens were conducted Absorbed energy, max load and deflection increased with increasing impact energy Tensile strength and work-to-fracture increased with increasing tensile strain rate Full field strain, cracking and localization was quantitatively studied using DIC Highly complex rate dependence of UHPC was revealed by nonuniform strain-rate field Abstract: The rate-sensitive properties of ultra-high performance concrete (UHPC) subjected to flexural and direct tensile loads were investigated. Dynamic flexural tests were performed by means of a drop hammer impact machine, whereas a servo-hydraulic system was utilized to conduct direct tension tests. The absorbed energy of the UHPC specimens under flexure increased from 0.74 to 4.49 J as the input energy varied from 6.7 to 67 J. The load-bearing capacity and maximum flexural deformation exhibited identical trends as the input energy increased. The high-speed tensile properties, including strength, ductility, and energy dissipation capacity, improved upon increasing the strain rate up to 100 s -1 . A nonuniform distribution of the deformation of UHPC specimens under high-speed tension was observed by identifying the zones of strain localization (near crack), uniform strain (far field), and shear lag (transition zone in between) using digital image correlation. The full-field data of displacement, strain, and strain rates were obtained and quantitatively evaluated. The results indicated that multiple mechanisms were involved in the rate-dependent behavior of the UHPC specimens.